Fisheries Management in Stanley Reservoir - A Case Analysis - Angela, S Agnes Daney; Immanuel, Sheela; Ananthan, P S; Anand, G Ajay; Krishnan, M (Fishery Technology, 2025)
Fisheries in reservoirs, play a significant role in the livelihood of rural communities. In this context, a study was undertaken in Stanley reservoir in Salem district of Tamil Nadu to understand management of fisheries in the largest reservoir in South India. An attempt was made to comprehend the problems encountered by the fishers. The Department of Fisheries takes lead role in the management of the reservoir. Rules and regulations are framed by the Department of Fisheries including annual stocking of fish seeds. Fishing in the Stanley reservoir is carried out by licensed fishers whose numbers are regulated by the Department of Fisheries. It was observed that mesh size regulations and closed seasons are not enforced strictly. Fishers need to sell the catch to the Fishermen Co-operative Marketing Society which gives them reasonable price. The major constraints perceived by the fishers were ‘fluctuating income’ and ‘poaching’.